Electronic-based UKM Mascot Branding to Strengthen Business Resilience after the Covid-19 Pandemic in Tempe Sanan Village, Malang City - Winarno, Agung; Agustina, Yuli; Damayanti, Erin Alida (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
The condition of the COVID-19 pandemic which has had a major impact on the sales growth of SMEs including the Sanan tempe village area, this service activity aims to try to revive business development conditions in the form of assistance in making electronic-based branding mascots. The stages used start from identifying real needs, FGDs, program planning, implementation and evaluation. The results of the activity in the form of a mascot are made with a cute and cute chibi style, the head is adapted from Sanan tempeh chips, with a banana leaf textured body. Everything is based on things that are related and very iconic of Sanan village. Then the mascot was named “Kinan” taken from the abbreviation Keripik Tempe Sanan, the mascot has been published through social media as part of branding the product.